FATWA LAJNAH BAHTSUL MASAIL (LBM) NAHDHATUL ULAMA TENTANG KEDUDUKAN PRESIDEN RI SEBAGAI WALIYUL AMRI DHARURI BISY SYAUKAH - Busyro, Busyro (Alhurriyah, 2011)
A fatwa is often influenced by social and political conditions that occur when the fatwa was born. It is possible also occurred in 1954 when Lajnah Bahtsul Masail Nahdhatul Ulama (NU-LBM) decided that the President of the Republic of Indonesia, Ir. Sukarno was waliyul amri dharury bisy syaukah. Although LBMNU fatwa based on fiqh, especially the fiqh Syafi’iyah. Someone says that the fatwa is influenced by maintaining position in Departemen Agama Religion Department) as managing board. Regardless that opinion, actually, NU maintains his power on Departemen Agama until 1971. This paper will simply want to research this fatwa and connecting it with the social realities when the fatwa is issued.